Personal characteristics, families, and community support associated with self-care behavior among Indonesian diabetic patients - Nurnaningsih Herya Ulfah; Septa Katmawanti; Andini Melati Sukma; Indana Tri Rahmawati; Pokkate Wongsasuluk; Lucky Radita Alma; Desy Ariwinanti (AOSIS, 2022)
Self-care management is the way to prevent the complication in diabetes. However, adherence to self-care management is low. This study aims to assess the association of personal characteristics, supports the system, including families and community, with the self-care behavior among diabetes patients. A cross-sectional study was used in this research. 158 participants were randomly selected based on the primary health care database in Malang City, Indonesia. There are eight parts of the questionnaire as the instruments in this study. Multivariate logistic regression was used to analyze the association of all independent variables with self-care behavior as a dependent variable. This study showed that 60.80% of respondents had complications while the less practicing self-care behavior was 46.84%. Furthermore, the ordinal regression logistic showed that duration of DM (OR:4.347, 95%CI 1.671-11.310), illness perception (OR: 0.028, 95%CI 6.090- 51.346), family supports (OR: 3.295, 95%CI 1.325-8.192), and community supports (2.802, 95%CI 1.209-6.493) were associated with self-care behavior among diabetes Mellitus. This finding can support the primary health care to involved family and community around diabetes patients to success the self-care management.